Uji Kualitas Briket Bioarang Berbahan Dasar Arang Kotoran Kambing, Arang Kotoran Sapi dan Arang Kotoran Ayam - Dwi F. Nahas; Oktovianus R. Nahak; Gerson F. Bira (Program Studi Peternakan, Fakultas Pertanian, Universitas Timor, 2019)
The purpose of this study was to determine the quality of bioarang briquettes processed using goat manure charcoal, cow manure charcoal and chicken manure charcoal. This research will be carried out in December-February 2019, this research will be conducted in 2 locations, where in the first stage bioarang briquettes are made in the Laboratory of the Faculty of Agriculture Timor of University, while the second phase is tested on the quality of bioarang briquettes conducted at the Laboratory of the Faculty of Animal Husbandry, Nutrition and Science Feed Technology IPB. This study used a completely randomized design (CRD) consisting of three treatments: Goat manure briquette (GMB) : Goat droppings 90% + starch 10%; cow dung briquettes (CDB) : 90% Cow dung + 10% starch and ; chicken manure briquette (CMB): 90% chicken manure + 10% starch and repeated 10 times so that there are 30 units of experimental unit. Anova variance results showed that the parameters of ash content, combustion rate and heating value showed significant differences (P <0.05). It was concluded that the best quality briquettes are briquettes made from basic ingredients of goat manure which produce lower water content (36.12%), ash content (38.62%) and calorific value (3525 cal / g) while the best combustion rate is given by cow dung briquettes (0.29g / sec).